2012
DOI: 10.1007/s11255-012-0297-7
|View full text |Cite
|
Sign up to set email alerts
|

Clamping renal artery alone produces less ischemic damage compared to clamping renal artery and vein together in two animal models: near-infrared tissue oximetry and quantitation of 8-isoprostane levels

Abstract: Renal ischemia injury from clamping the renal artery alone was significantly less than clamping artery/vein together demonstrated in two different techniques. Recovery of oxygen saturation was twofold faster, and mean post-clamp 8-isoprostane levels demonstrated a 1.54-fold decrease with clamping renal artery alone compared to clamping artery/vein together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…All of the above-mentioned histological damage was observed in three ischaemic groups of the present study but with different intensities: BIR-V group >> BIR-P group > BIR-A group. Due to increased use of laparoscopic partial nephrectomy for renal tumour resection, during which temporary renal blood flow stoppage is required, several studies have compared kidney damage induced by occluding pedicle with renal artery only via laparoscopy versus open surgery in humans (Gong et al, 2008;Liu et al, 2013) and large animals (Colli, Wang, Johnsen, Grossman, & Lee, 2013;Orvieto et al, 2007;Schuler et al, 2008;Tracy et al, 2010). It was suggested that probably negated the benefit of renal artery clamping (Orvieto et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the above-mentioned histological damage was observed in three ischaemic groups of the present study but with different intensities: BIR-V group >> BIR-P group > BIR-A group. Due to increased use of laparoscopic partial nephrectomy for renal tumour resection, during which temporary renal blood flow stoppage is required, several studies have compared kidney damage induced by occluding pedicle with renal artery only via laparoscopy versus open surgery in humans (Gong et al, 2008;Liu et al, 2013) and large animals (Colli, Wang, Johnsen, Grossman, & Lee, 2013;Orvieto et al, 2007;Schuler et al, 2008;Tracy et al, 2010). It was suggested that probably negated the benefit of renal artery clamping (Orvieto et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…n = 7 in each group. Due to increased use of laparoscopic partial nephrectomy for renal tumour resection, during which temporary renal blood flow stoppage is required, several studies have compared kidney damage induced by occluding pedicle with renal artery only via laparoscopy versus open surgery in humans(Gong et al, 2008;Liu et al, 2013) and large animals(Colli, Wang, Johnsen, Grossman, & Lee, 2013;Orvieto et al, 2007;Schuler et al, 2008;Tracy et al, 2010). ↔, Bowman's space; *, intratubular proteinaceous cast; ×, vascular or haemorrhagic congestion; C, collecting duct; D, distal tubule; G, glomerulus; P, proximal tubule; T, thick ascending limb detachment of viable cells.…”
mentioning
confidence: 99%
“…Renal ischemic time should be less than 20 minutes, otherwise renal injury may be caused [3]. A study in swines showed that clamping renal artery alone results in less ischemic damage of the organ [2], however, dissection to separate the renal artery and vein is necessary [3], increasing surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…Urine culture was positive for coagulase-negative Staphylococcus sp., susceptible to multiple classes of antibiotics. The patient remained hospitalized receiving fluid therapy with lactated Ringer's solution 1 (40 mL/kg/day IV), omeprazole 2 (1 mg/kg q 24h IV), maropitant 3 (1 mg/kg q 24h SC) and tramadol 4 (3 mg/kg q 8h SC). Enrofloxacin 5 (5 mg/kg q 24h IV) was prescribed based on urine culture and sensitivity testing.…”
Section: Casementioning
confidence: 99%
“…For clamping of the hilum, our preference is to place two bulldog clamps on the renal artery alone, leaving the vein open. Previous studies had shown a benefit of hemostasis, as well as optimizing recovery of renal function and minimizing ischemia …”
Section: Instrumentationmentioning
confidence: 99%